Implementasi Prinsip Hifzh An-Nasl terhadap Penggunaan Teknologi In Vitro Fertilization (IVF) - Mella Yolanda Sari; Adlan Sanur Tarihoran (KIPS Institute Bukittinggi, 2025)
This study discussed the implementation of the hifzh an-nasl principle within the framework of maqashid shariah concerning the use of in vitro fertilization (IVF) technology. IVF is a modern medical solution for married couples experiencing fertility issues. However, from an Islamic perspective, its application must remain within the boundaries of Shariah, particularly in protecting lineage (nasl) from nasab confusion and violations of religious norms. This research uses a qualitative-descriptive approach through literature studies to examine the extent to which IVF practices align with the principle of lineage protection in maqashid shariah. The findings indicate that IVF is permissible under Islamic law as long as it is conducted between legally married couples and does not involve any third party in the fertilization process. Thus, implementing the hifzh an-nasl principle in this technology is crucial to ensure that modern reproductive technologies remain consistent with Islamic values.